Pre-clinical evaluation of a third generation absorbable antibacterial envelope. (19th May 2022) - Christie, M; Love, C; Hanna, I; Thomas, G; Greenspon, A; Chen, S; Sanders, M; Bauer, C; Christopherson, M; Balaji, V; Skulsky, S; Sohail, M
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Medtronic Background: An absorbable antibacterial envelope (TYRX), which stabilizes cardiac implantable electronic devices (CIEDs) was shown to significantly reduce infections in a large randomized controlled trial (WRAP-IT). A 3rd generation envelope (T3) is being developed to improve the implanter experience and enable smoother device insertion with a redesigned, multifilament mesh, an enhanced form factor, and identical polymer coating and antibiotic concentrations as the currently available 2nd generation envelope (T2). Purpose: To compare drug elution profiles of T3 vs T2 and evaluate the efficacy of T3 against bacteria commonly known to be associated with CIED infections. Methods: The T3 drug elution profile was assessed in vitro by evaluating the amount of each drug, minocycline and rifampin, released at a given timepoint using an accelerated dissolution method. For comparative analysis with T2, elution curve equivalency was based on similarity factor values (f2) of ≥50 per FDA guidance. An in vivo elution study was also conducted (per the Principles of Laboratory Animal Care [NIH Publication no. 85-23 revised 1985]) to ensure drug concentrations met the minimal inhibitory concentration (MIC) through 7 days. Substantial equivalence was defined as rifampin and minocycline concentrations above MIC at 2hr post-implant and sustained through 7 days. In a further animal model, 12 pockets were created in 6 rabbits, for CIED insertion with and without T3 envelopes, to evaluate efficacy against gram+ and gram- bacteria. At day 7, implant sites were evaluated for signs of infection via macroscopic observations and microbial recovery procedures. A Fisher's Exact Test was used for comparisons. Results: The T3 envelope showed a similar elution profile to T2 in vitro (Figure) with f2 >50 (range 76-84). In the in vivo assessment, the T3 envelope eluted both antibiotics above the MIC at 2hr post-implant with sustained elution through 7 days, consistent with historical T2 performance. Further bacterial challenge studies in vivo showed a statistically significant reduction (p<0.05) in infections with 0/6 infected pockets in the CIED + T3 group vs 6/6 infected pockets in the CIED only group consistent with T2 performance (Table). Conclusion: The 3rd generation absorbable antibacterial envelope demonstrated equivalent pre-clinical performance compared to the 2nd generation envelope as antibiotic elution curves were equivalent, elution was sustained at concentrations above MIC for 7 days, and infection rates were significantly reduced compared to no envelope. These results suggest equivalent clinical performance could be expected with the newly designed envelope.